THE PROBLEMS OF SERBIAN SELF-DETERMINATION IN FOREIGN POLICY: THROUGH THE THORNS TO THE “STARS” OF THE EUROPEAN UNION - M. M. Lobanov; J. Z. Lobanova (Сравнительная политика)
The article deals with the features of contemporary political development of Serbia, including the main areas of cooperation with the European Union (EU). Since the early 2000s the strategic priority of the country's foreign policy is participation in the European integration process, which is accompanied by support of consistent and pragmatic relations with the other key partners, primarily with Russia. The principle of multi-vector foreign policy has been developed since the fi rst half of the 2010s, but its use is treated with the lack of uniqueness by different social strata and political movements. Mechanisms of acceleration or slowing down the integration process are used by offi cial Brussels depending on the current aims and political conjuncture (for example, to weaken Russian infl uence in the country and in the region). However, despite the success achieved on the path to the EU accession and the favorable dynamics of negotiation process, the level of support of pro-European policy has been decreasing in Serbian society since the end of the 2000s. The main challenges of the near future, in addition to the growth of euroscepticism, include problems of institutional harmonization with the EU and the compliance with the Copenhagen criteria, the enforcement of the Brussels agreement with Pristina, as well as maintaining of balanced foreign policy.